Architectural and Cultural through Islamic Social Values in the Spatial Practices of Traditional Melayu Dwellings: Case Study- Rumah Penghulu Demang Abdul Ghani in Merlimau, Melaka - Alice Sabrina Ismail (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2026)
This paper investigates how the cultural and Islamic social values of the Melayu Melaka community shape, regulate, and sustain the spatial, material, and symbolic dimensions of residential architecture in Malacca. Rooted in centuries of historical stratification, processes of Islamisation, mercantile cosmopolitanism, and locally embedded adat, the Melayu Melaka worldview is articulated through the organisation of domestic space, dwelling practices, material culture, and architectural ornamentation. Adopting a qualitative, interpretive research methodology informed by architectural anthropology, vernacular architecture studies, and cultural history, the study argues that core cultural and Islamic social values—such as propriety, religiosity, communal cooperation, and social harmony—are materially and spatially inscribed within house typologies, spatial sequencing, construction techniques, threshold rituals, and the aesthetic language of domestic ornamentation. Through an analysis of classical kampung houses, the paper demonstrates that these values not only inform architectural form-making but also operate as cultural drivers that mediate social relations, reinforce collective identity, and regulate everyday life. The study concludes by positioning the Melayu Melaka house as a form of living moral architecture, continuously negotiated across generations, and emphasises that the safeguarding of this moral–architectural heritage is essential for sustaining cultural resilience amid modernisation and the pressures of global tourism.